Pengaruh Model Pendampingan Deteksi Dini Terhadap Kemampuan Guru PAUD Dalam Melaksanakan Deteksi Dini Pertumbuhan Dan Perkembangan Anak PAUD di Wilayah Puskesmas Beji Depok - Suryati B; Bara Miradwiyana (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Impaired growth and development of children can be identified by early detection as prevention, prevention, stimulation and development. This study aims to determine the effect of early detection assistance models on the ability of early childhood education (PAUD) teachers in implementing early detection of early childhood growth and development. The research method uses pretest and posttest design with control group. Providing training and mentoring for PAUD teachers using the Stimulation of Detection and Early Intervention Growing Swell (SDIDTK)/ Child Development Pre-screening Questionnaire (KPSP) for the intervention group while for the control group for PAUD teachers by being given a KPSP booklet after the posttest. The results of the analysis showed that there were differences in scores of PAUD teachers' knowledge and skills in stimulating early childhood growth and development (p=0.001) between the intervention group and the control group after the mentoring model intervention. The knowledge of PAUD teachers who are given a mentoring model is better than the control group, there are significant differences in improving the ability of PAUD teachers to do early detection in children compared to the control group. PAUD teachers who are given the intervention of the mentoring model.